Pengaruh Harga Dan Kualitas Produk Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Pelanggan Kopi Hashtag, Kota Malang) - Akmal Rizky Pratama; Rois Arifin; Andi Normala Dewi (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The studied aiming to be determining serviced qualitied, producted qualitied and promotional mixing on purchased decisioning for Pada pelanggan Kopi Hashtag Malang products, Malang College. Goods quality can attract customer's special interest. In order to face the competition, a company implements a marketing strategy for the goods produced. In a position to try to increase competition for similar goods and the behavior of customers who prefer new variants of goods issued by competitor issuers for satisfaction, more benefits & curiosity (Purwita, 2019). The company must also show that product quality must be in Barangsi because as well as growing the reputation quality of the issuer, it will increase so that the issuer gets a good reputation in the eyes of customers. On the other hand, customers will always remember by definition the quality of the goods is good, even customers will decide to buy the same goods again. In deciding a transaction, one of the factors that will be reviewed by the customer is price. Award Determination Strategy is a fundamental function that must be carried out by a company in responding to the market. Awards are also by definition one of the points taken into consideration by customers in determining transaction policies on goods (Kotler, 2005:18). Where the award is the amount of money that the customer must give fish in order to obtain or use an item or service. In addition, awards will be an important consideration for customers in deciding their transactions, customers will compare the goods awards of their choice, then whether such awards are appropriate or not with the value of the goods and the amount of money that must be spent, so of course, customers choose other customer awards (awards). Keywords: Customer Loyalty, Customer Satisfaction, Price, Product Quality